Pengaruh Motivasi Kerja Sistem Informasi Akuntansi dan Etos Kerja Islami Terhadap Kinerja Karyawan - Nenden Humairoh; Dadan Soekardan (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to determine the effect of accounting information systems on work motivation and Islamic work ethic on employee performance. The population used is Islamic banking companies in the city of Bandung as many as 4 Islamic banks. The method used in this research is descriptive and associative methods with a survey approach and using primary data. The statistical analysis used in this study is multiple linear regression analysis, correlation, hypothesis testing using t- test and f-test and analysis of the coefficient of determination with the help of the IBM SPSS Statistical Version 20 program. Based on the results of research conducted can be known the effect of accounting information systems work motivation and Islamic work ethic on employee performance.